Colombia's national policy of environmental education: a critical discourse analysis. Issue 4 (3rd April 2021) - Mejía-Cáceres, María Angélica; Huérfano, Alejandra; Reid, Alan; Freire, Laísa María
Abstract: This article explores how an environmental education policy text comes to be constituted by discursive strategies that reproduce or challenge particular ideologies of environmentalism in relation to education. Using a qualitative analysis of discourses in the National Policy of Environmental Education of Colombia (NPEEC), we examine how these can be traced to a range of stakeholders. Unsurprisingly, key findings include that the discourses present in the policy strongly reflect broader policy agendas circulating in the country, such that the NPEEC falls in line with neoliberal policy prescriptions for addressing environmental challenges. The NPEEC also omits and transforms certain discourses from the environmental education researcher community, particularly when these offer critical and alternative viewpoints for tackling environmental issues through education. The article illuminates how these gaps and movements might be a result of global pressure on local governments, and how the contributions of nationally-recognised environmental education research and researchers have been reduced in the text of the NPEEC. We conclude this represents a problematic relation between research and policy, and discuss the features of this 'disidentification'. Abstract :